Comparative study of efficacy of commercial anthelmintic response against gastrointestinal nematodes in goats of Jhenidah district, Bangladesh - Kumar Halder, Prodip; Kumar Sarker, Biplob; Shah Alam, Md.; Nime, Jannatun; Tareq Mussa, Md.; Mostafijur Rahman, Md.; Kumer Chakraborty, Bipul; Harun-ur-Rashid, SM. (International Journal of Biological Research, 2019)
Background: Parasitic disease constitutes 60-70% diseases affecting the animals and has serious economic implication in livestock entrepreneurship by direct and indirect production loss. Indiscriminate use of anthelmintic drugs has made the situation even more precarious. A similar problem was encountered in goat from Holidhani, Jhenidah, where goats with complain of intermittent diarrhea and loss of body condition was reported despite of routine deworming.Objective:Â Determining the efficacy of conventional anthelmintics used and its comparison with some unexploited antiparasitic drugs for the same reason.Methods: Sixty-five goats were divided into five groups. Group A goats were kept as the control, Group B (I, II, III), group C (IV, V, VI), group D (VII, VIII, IX) and group E (X, XI, XII) goats were treated with levamisole, albendazole, fenbendazole and ivermectin respectively. All the treated and control goats were kept, housed for 21 days after the first treatment. Fecal samples were collected and counted on 1st, 7th, 14th and 21st day by using McMaster counting method.Results: Among the three doses of levamisole, albendazole, fenbendazole and ivermectin, the doses of 7.5, 7.5, 5.0 and 0.2 mg/kg body weight, body weight were found to be most effective against gastrointestinal nematodes in goats with a maximum reduction of fecal egg count to the extent of 95.38, 97.13, 98.08 & 99.16 percent respectively.Conclusion: The study revealed low efficacy of levamisole and hence ivermectin is a better drug than albendazole and fenbendazole to control gastrointestinal nematodes in goats.Â